Reading Writing Right Essays Presented in Honour of Prof Elna Mouton - Punt, J. 1962- (Stellenbosch African Sun Media, 2018)
Intro -- Acknowledgements -- Preface -- Introduction -- Section A - Right Reading -- Chapter 1: Reading Rightly? -- Chapter 2: Some thoughts on the De-centred Reader -- Chapter 3: From "One-way" Authoritative Discourse to Critical, Open Dialogue(s) -- Chapter 4: Further Interrogation of the Comparative Paradigm in African Biblical Scholarship -- Chapter 5: Experiencing the Fourth Gospel -- Chapter 6: Tobit through the Lens of Trauma -- Chapter 7: Questioning the "Natural Given -- Section B | Reading Writings -- Chapter 8: In Search of the Female Sage -- Chapter 9: Living with Integrity and Wisdom? -- Chapter 10: Reading the Tamar Story through a Postcolonial Lens -- Chapter 11: The Perfect Believer in Manly Religion (James 1) -- Chapter 12: Where Heaven and Earth Meet -- Chapter 13: The Pathos of New Testament Interpretation -- Section C | Readings and Writings -- Chapter 14: An Enigmatic Longing -- Chapter 15: On Leadership in Vulnerability -- Chapter 16: Funerary Customs in First-century Mediterranean Culture -- Chapter 17: Plotting Pauline Travels in an Imperial Setting.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books